Electronic properties of Cr-, B-doped and codoped SrTiO3 - Stashans, A. (2017)
Spin-polarized density functional theory (DFT) computations have been carried out to investigate Cr-, B-doping as well as codoping in the SrTiO3 crystal. Impact of the oxygen vacancy as an intrinsic point defect has been also taken into consideration. In order to describe more precisely 3d electrons of the Ti and Cr atoms, Hubbard-like U term in the DFT has been introduced. Outcomes of the calculations reveal occupied states within the forbidden energy region arguing that these in-gap states might be responsible for visible light photocatalysis in the SrTiO3. Structural and magnetic features of the doped and codoped material are discussed as well. © 2016 Elsevier Ltd